Estudo dos amidos de mandioca nativo, modificados e modificados combinados por via química para utilização na indústria alimentícia - Ribeiro, Ana Paula Loura (2011)
The starch is a thickener and gelling agent most commonly used in food industry allowing the development of a large number of products, however, their industrial applications are limited mainly due to their use in native (unmodified). Modified starches that have specific properties able to give attributes to the development of a quality product is a subject of growing interest. The objective of this research was to study the starch from cassava (Manihot esculenta, Crantz) modified by acid hydrolysis reactions, Succinilação, acetylation, interbreeding of links, and the combination of acid hydrolysis with each of those reactions, and compare their properties with the native starch for use in the food industry. It was found that the native starch has low impurity with granules and some circular concave-convex with most measuring 15μ and that the modifications did not affect the grain structure. The native starches, acetylated and succinyl provide a high capacity for water absorption, swelling power, also more viscous pastes available for use in bakery products and meat products and the first two had the lowest temperature of pulp, representing favorable potential for use in food preparation snapshot. The hydrolyzed starch, hydrolyzed-acetylated. The hydrolyzed starch, hydrolyzed-acetylated and hydrolyzed-succinyl higher values solubility and folders clearer and can be used in jams, pie fillings, jams or jelly beans. In contrast, the hydrolyzed starch has a lower capacity for oil absorption favoring its use in fried products. The starch and hydrolyzed-interbreed interbreed, have great resistance to temperature rise can be used in foods to be sterilized. And besides, these starches as well as the hydrolyzed and hydrolyzed, acetylated, had low values of breakdown, Showing high thermal and mechanical stability and also showed reduced tendency to retrogradation, which are ideal for use in foods requiring storage for long periods at low temperatures.